D2+DD'-2D'2=(y-1)ex
D=m
D'=1
m2+m-2=0
m2-m+2m-2=0
(m+2)(m-1)=0
m=-2 or 1
The roots remain distinct
C.F=f1(y-2x)+f2(y+x)
P.I="\\frac{1}{D^{2}+DD'-2D'^{2}}\u2022(y-1)e^{x}"
="\\frac{1}{(D+2D')(D-D')}\u2022(y-1)e^{x}"
="[\\frac{1}{D+2D'}][\\frac{1}{D-D'}\u2022(y-1)e^{x}]"
D-mD'=D-D'
"\\therefore m=1"
y=C-mx=C-x
P.I="\\frac{1}{D+2D'}[\\int (C-x-1)e^{x}dx]"
="\\frac{1}{D+2D'}[(C-x-1)e^{x}-e^{x}]"
="\\frac{1}{D+2D'}[(y-1)e^{x}-e^{x}]"
D-mD'=D+2D'
"\\therefore m=-2"
y=C-mx=C+2x
P.I="\\int ((C+2x-1)e^{x}-e^{x})dx"
=(C+2x-1)ex-(2)ex--ex
=(y-1)ex--2ex--ex
=(y-4)ex
Complete solution,Z=C.F+P.I
="f_1(y-2x)+f_2(y+x)+(y-4)e^{x}"
Comments
Leave a comment